The Effect of Compassion-Focused Therapy on the Symptoms of Intrusion, Arousal, and Avoidance of Post-Traumatic Stress Disorder in Nurses - Milad Mohammadi; , Mosayeb Mosayeb Yar Mohammadi Vasel; hossein mohagheghi; Gholam Hossein Fallah Nia (پژوهش‌های کاربردی روانشناختی)
This study aimed to investigate the effect of compassion-focused therapy (CFT) on the symptoms of intrusion, arousal, and avoidance in post-traumatic stress disorder (PTSD) in nurses at Farshchian Hospital in Hamadan in 2021. The research design is quasi-experimental, with a control group and a pre-test-post-test, and the research method is applied in terms of purpose. The target population includes the nurses of Farshchian Heart Hospital in 2021. The purposive sampling method was employed to select 30 nurses (23 women and 7 males) for this study. The nurses were randomly assigned to the experimental and control groups. The experimental group underwent focused compassion treatment for eight 45-minute sessions. Research tools include the PTSD checklist (PCL). The data were analyzed using SPSS software version 23 for covariance analysis. The results showed that post-traumatic stress disorder was significantly impacted by compassion-focused treatment (p <0.01, F = 60.56). Therefore, it can be suggested that compassion-focused therapy, which employs techniques such as compassionate self-correction, emotional system regulation, and mindfulness, is a viable approach to alleviating the symptoms of intrusion, arousal, and avoidance in post-traumatic stress disorder.